2012
DOI: 10.5551/jat.14621
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Management of Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a highly prevalent autosomal dominant hereditary disease, generally characterized by three major signs, hyper-low-density-lipoprotein (LDL) cholesterolemia, tendon/skin xanthomas and premature coronary artery disease (CAD). Because the risk of CAD is very high in these patients, they should be identified at an early stage of their lives and started on intensive treatment to control LDL-cholesterol. We here introduce a new guideline for the management of FH patients in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
166
0
21

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(189 citation statements)
references
References 87 publications
(59 reference statements)
2
166
0
21
Order By: Relevance
“…In a Korean study, 31 patients with pathogenic mutations in the LDLR, APOB, and PCSK9 genes were found in 97 patients identified with LDL-C 190 mg/dL, combining with xanthoma or an FHcompatible family history 32) . Of the 31 patients, 27 had mutations in the LDLR gene, two had mutations Abbreviations: HeFH heterozygous familial hypercholesterolemia; HoFH homozygous familial hypercholesterolemia; CAD coronary artery disease; TC total cholesterol; LDL-C low-density lipoprotein cholesterol; TG triglyceride treatment of dyslipidemia 31) . China's 2007 guidelines for dyslipidemia lacked a separate section for FH and systematic recommendations for the diagnosis, detection, and treatment of FH 44) .…”
Section: Genotypes Of Fh Reported In Asian Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Korean study, 31 patients with pathogenic mutations in the LDLR, APOB, and PCSK9 genes were found in 97 patients identified with LDL-C 190 mg/dL, combining with xanthoma or an FHcompatible family history 32) . Of the 31 patients, 27 had mutations in the LDLR gene, two had mutations Abbreviations: HeFH heterozygous familial hypercholesterolemia; HoFH homozygous familial hypercholesterolemia; CAD coronary artery disease; TC total cholesterol; LDL-C low-density lipoprotein cholesterol; TG triglyceride treatment of dyslipidemia 31) . China's 2007 guidelines for dyslipidemia lacked a separate section for FH and systematic recommendations for the diagnosis, detection, and treatment of FH 44) .…”
Section: Genotypes Of Fh Reported In Asian Populationsmentioning
confidence: 99%
“…In Asia, Japan and China have developed their own diagnostic criteria 26,29,30) . The FH diagnostic criteria issued by Japanese scientists included three key diagnostic components: LDL-C level, tendon xanthoma or xanthoma tuberosum, and family history 31) . The clinical criteria developed by China can be found in the textbook Clinical Coronary Heart Disease, which included two key diagnostic components: TC/LDL-C level and patients or family members with tendon xanthoma 29) .…”
Section: Frequency Of Fh In Asian Populationsmentioning
confidence: 99%
“…Учитывая трудности в достижении целе-вого уровня холестерина ЛПНП, статины часто ком-бинируются с эзетролом -препаратом, препятству-ющим всасыванию липидов в кишечнике. Результаты большого клинического исследования с включением более 700 пациентов с семейной гиперхолестерине-мией показали, что комбинация симастатина с эзе-тролом позволяет дополнительно снизить уровень холестерина ЛПНП еще на 20% [26]. Препарат назна-чается с 10 лет, комбинируется со статинами, хорошо переносится [27].…”
Section: лечениеunclassified
“…При этом возможна регрессия ксантом, регресс атеросклеротического поражения сосудов и замедление прогрессирования атероскле-роза [6,26,[32][33][34]. Обычно процедура проводится 1 раз в 2 нед у детей старше 5 лет [6,26,32], хотя хо-рошие результаты были получены даже у детей бо-лее раннего возраста с массой тела более 13,5 кг [33]. К сожалению, в настоящее время эта процедура име-ет ограниченное применение в педиатрической прак-тике в России.…”
Section: лечениеunclassified
“…This provides an early foundation for the development of expert guidelines, essential services, and new models of care in Asian countries. Guidelines and diagnostic criteria for FH have hitherto been produced by Japan 17) and Australasia 18) ; Hong Kong 19) and South Korea 20) also recently communicated their experiences in managing FH. This is a good start to a long journey.…”
mentioning
confidence: 99%